Nod‐like receptors are critical for gut–brain axis signalling in mice. (27th November 2019) - Pusceddu, Matteo M.; Barboza, Mariana; Keogh, Ciara E.; Schneider, Melinda; Stokes, Patricia; Sladek, Jessica A.; Kim, Hyun Jung D.; Torres‐Fuentes, Cristina; Goldfild, Lily R.; Gillis, Shane E.; Brust‐Mascher, Ingrid; Rabasa, Gonzalo; et al.
Abstract : Key points: Nucleotide binding oligomerization domain (Nod)‐like receptors regulate cognition, anxiety and hypothalamic–pituitary–adrenal axis activation. Nod‐like receptors regulate central and peripheral serotonergic biology. Nod‐like receptors are important for maintenance of gastrointestinal physiology. Intestinal epithelial cell expression of Nod1 receptors regulate behaviour. Abstract: Gut–brain axis signalling is critical for maintaining health and homeostasis. Stressful life events can impact gut–brain signalling, leading to altered mood, cognition and intestinal dysfunction. In the present study, we identified nucleotide binding oligomerization domain (Nod)‐like receptors (NLR), Nod1 and Nod2, as novel regulators for gut–brain signalling. NLR are innate immune pattern recognition receptors expressed in the gut and brain, and are important in the regulation of gastrointestinal physiology. We found that mice deficient in both Nod1 and Nod2 (NodDKO) demonstrate signs of stress‐induced anxiety, cognitive impairment and depression in the context of a hyperactive hypothalamic–pituitary–adrenal axis. These deficits were coupled with impairments in the serotonergic pathway in the brain, decreased hippocampal cell proliferation and immature neurons, as well as reduced neural activation. In addition, NodDKO mice had increased gastrointestinal permeability and altered serotonin signalling in the gut following exposure to acute stress. Administration of the selective serotonin reuptake inhibitor, fluoxetine, abrogated behavioural impairments and restored serotonin signalling. We also identified that intestinal epithelial cell‐specific deletion of Nod1 (VilCre + Nod1 f/f ), but not Nod2, increased susceptibility to stress‐induced anxiety‐like behaviour and cognitive impairment following exposure to stress. Together, these data suggest that intestinal epithelial NLR are novel modulators of gut–brain communication and may serve as potential novel therapeutic targets for the treatment of gut–brain disorders. Key points: Nucleotide binding oligomerization domain (Nod)‐like receptors regulate cognition, anxiety and hypothalamic–pituitary–adrenal axis activation. Nod‐like receptors regulate central and peripheral serotonergic biology. Nod‐like receptors are important for maintenance of gastrointestinal physiology. Intestinal epithelial cell expression of Nod1 receptors regulate behaviour.